V. OLIVEIRA - Urban Morphology: An Introduction to the Study of the Physical Form of Cities - García-Pérez, Sergio (ZARCH, 2018)
Vitor Oliveira Urban Morphology: An Introduction to the Study of the Physical Form of Cities Springer International Publishing, Cham (Suíza), 2016. Idioma: inglés. DOI: 10.1007/978-3-319-32083-0. ISBN: 9783319320816